2021
DOI: 10.1111/jsap.13349
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of gross and histopathologic lesions associated with closed chest cardiopulmonary resuscitation in dogs

Abstract: To investigate and characterise the incidence of iatrogenic complications secondary to closed chest cardiopulmonary resuscitation in dogs.Materials and MethOds: Necropsy reports and histologic sections of tissues were retrospectively examined from 180 dogs that had received closed chest cardiopulmonary resuscitation to determine lesions associated with resuscitation. results: The most common complication was pulmonary haemorrhage (81/163, 49.7%, 95% confidence interval: 42.1 to 57.3), although only nine dogs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In adult chickens, CPR compressions did not appear to frequently cause gross pathological changes (eg, massive hepatic fractures, pulmonary hemorrhage, or follicular rupture), although 2 chickens did experience small hepatic fractures at the margins of the liver lobes. In dogs, pulmonary hemorrhage is frequently noted after CPR and can often result in post‐ROSC complications and death 18–20 . The apparent lack of pulmonary hemorrhage in the current study may result from the relatively “protected” dorsal position of avian lungs 7 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In adult chickens, CPR compressions did not appear to frequently cause gross pathological changes (eg, massive hepatic fractures, pulmonary hemorrhage, or follicular rupture), although 2 chickens did experience small hepatic fractures at the margins of the liver lobes. In dogs, pulmonary hemorrhage is frequently noted after CPR and can often result in post‐ROSC complications and death 18–20 . The apparent lack of pulmonary hemorrhage in the current study may result from the relatively “protected” dorsal position of avian lungs 7 .…”
Section: Discussionmentioning
confidence: 66%
“…In dogs, pulmonary hemorrhage is frequently noted after CPR and can often result in post-ROSC complications and death. [18][19][20] The apparent lack of pulmonary hemorrhage in the current study may result from the relatively "protected" dorsal position of avian lungs. 7 Nevertheless, it remains possible that overexuberant compressions on their own or in combination with an individual chicken's pathology (eg, hepatic lipidosis) could result in significant internal injuries.…”
Section: Discussionmentioning
confidence: 72%
“…In 2021, a study investigated iatrogenic lesions after CPR in dogs and found an overall occurrence of hemopericardia in 4.8% of patients. Notably, all 8 patients who received ICI exhibited complications, including hemopericardium, hemothorax, hemomediastinum, and cardiac and pulmonary hemorrhage ( 8 ). In the cat reported here, both scenarios could be possible.…”
Section: Discussionmentioning
confidence: 99%
“…As potential causes for PE, feline infectious peritonitis (FIP) ( 2 , 3 ), congestive heart failure ( 4 ), neoplasms such as lymphoma ( 5 ) or sarcoma ( 6 ), and inflammatory diseases ( 7 ) are described. Regardless of this, cardiopulmonary resuscitation (CPR) and especially intracardiac injections (ICIs) are known risk factors for iatrogenic damage to the heart and pericardium in dogs, potentially leading to PE ( 8 ). Pericarditis can be linked to conditions such as bacterial infections ( 9 11 ), FIP ( 2 ), migrating foreign bodies ( 12 , 13 ), hypereosinophilic syndrome ( 14 ), lymphoma ( 15 ), and peritoneopericardial diaphragmatic hernia repair ( 16 ).…”
Section: Introductionmentioning
confidence: 99%